Interaction of Bartonella henselae with the Murine Macrophage Cell Line J774: Infection and Proinflammatory Response - Musso, Tiziana (American Society for Microbiology, 2001)
Bartonella henselae is the causative agent of cat scratch disease (CSD), a self-limiting condition characterized by a subacute regional lymphadenopathy that may develop into disseminated bartonellosis in immunocompromised subjects. Mice experimentally infected with B. henselae display typical liver and spleen granulomas rich in T cells and macrophages. So far there are no data on the interaction between bartonellae and macrophages. In order to clarify this topic, we investigated the interaction of B. henselae with J774, a mouse macrophage cell line. Analysis of bacterial uptake by functional assays and transmission electron microscopy indicates that bartonellae can enter and survive inside J774. Entry occurred within 30 min postinfection and reached a plateau at 160 min. Infection of J774 was followed by a dose-dependent release of the proinflammatory cytokines tumor necrosis factor alpha, interleukin 1β (IL-1β), and IL-6. Bartonellae persisted intracellularly without loss of viability for at least 8 h, and their number slightly decreased 24 h postinfection. Gamma interferon (IFN-γ) treatment of J774 significantly decreased the number of recoverable bacteria at 8 and 24 h. This enhancement of macrophage bactericidal activity was associated with nitric oxide (NO) release and was prevented by the addition of the competitive inhibitor of NO synthesis N(G)-monomethyl l-arginine. These findings suggest that IFN-γ-mediated activation of macrophages may be important for the clearing of B. henselae infection and that anti-B. henselae microbicidal activity of IFN-γ-activated macrophages is mediated to a large extent by NO production.